Olanzapine-induced acute pancreatitis - Birol Baysal; Yusuf Kayar; Aykut Özmen; Maged ElShobaky; Nabila Mahdi; Ali Tüzün İnce; Ahmet Danalıoğlu; Hakan Şentürk (Turkish Journal of Gastroenterology, 2019)
-